Legal Protection of Female Inmates in Pregnancy, Childbirth, and Breastfeeding in Correctional Institutions - Bintoro, Kusumo Wahyu; Santoso, Budi; Ispriyarso, Budi (JURNAL AKTA, 2024)
This research aims to analyze the condition of imprisoned women who are pregnant, giving birth, and breastfeeding within correctional facilities by examining the relevant regulations and case observations. This research uses a normative-empirical approach. This research is conducted by reviewing literature data supported by the studied cases. The data obtained are analyzed by qualitative methods and presented descriptively. The conclusions of the research are: 1) The rights of these prisoners are not fully met. There is an imbalance in facilities and treatment among different prisons.2) The regulations on the rights of prisoners who are pregnant, giving birth and breastfeeding in Indonesian law are still inadequate and insufficient as outlined by international convention